2019
DOI: 10.1038/s41598-019-40772-7
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Results of a Single Center Database for Stentless Xenograft Use in a Full Root Technique in Over 970 Patients

Abstract: Our aim was to analyse the hospital outcome for the worldwide largest series of stentless bioroot xenografts (Medtronic Freestyle) as full root replacement in a single centre over a period of 18 years. Retrospective data analysis was performed for the entire cohort of patients undergoing aortic root surgery with the Medtronic Freestyle valve prosthesis. Logistic regression analysis was performed to analyse predictors of in-hospital mortality. 971 patients underwent aortic full root replacement with the Medtron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The rate of most early complications, including reoperation for bleeding or tamponade, was comparable with previous reports. 2,[9][10][11][14][15][16]18,19,[21][22][23][24][26][27][28][29]31,32,37 However, the number of cerebrovascular events in the type A dissection and endocarditis groups were 22.4% and 10.2%, respectively, compared with up to 10% observed in other studies of these indications. 27,31,32 Some studies included only permanent stroke whereas others did not specify inclusion (eg, transient ischemic attacks or stroke without sequelae).…”
Section: Early Complicationsmentioning
confidence: 57%
“…The rate of most early complications, including reoperation for bleeding or tamponade, was comparable with previous reports. 2,[9][10][11][14][15][16]18,19,[21][22][23][24][26][27][28][29]31,32,37 However, the number of cerebrovascular events in the type A dissection and endocarditis groups were 22.4% and 10.2%, respectively, compared with up to 10% observed in other studies of these indications. 27,31,32 Some studies included only permanent stroke whereas others did not specify inclusion (eg, transient ischemic attacks or stroke without sequelae).…”
Section: Early Complicationsmentioning
confidence: 57%
“…Indeed, in their systematic review Sherrah et al, reported an in-hospital mortality of 5.2% after Freestyle implantation (10). When our results are placed into perspective, and consideration is made of mortality rates in combined aortic root procedures, high-risk patients, reoperations, or freestyle prosthesis implantation in destructive endocarditis, the outcomes could be considered comparable (11)(12)(13)(14)(15).…”
Section: Discussionmentioning
confidence: 74%
“…Smith et al 20 demonstrated the use of the Medtronic Freestyle bioprosthesis in TAAD with satisfactory early and midterm outcomes in 24 patients, although this was not compared with a valid control. Similarly, larger centers have reported the use of porcine stentless aortic roots as the biological conduit of choice in TAAD with good results 21,22 . Despite this, there is limited evidence comparing the use of porcine stentless aortic bioprosthesis with alternative root surgery in TAAD.…”
Section: Discussionmentioning
confidence: 99%